Theorizing Surveillance in the UK Crime Control Field - McCahill, Michael (Media and Communication, 2015)
Drawing upon the work of Pierre Bourdieu and Loic Wacquant, this paper argues that the demise of the Keynesian Welfare State (KWS) and the rise of neo-liberal economic policies in the UK has placed new surveillance technologies at the centre of a reconfigured “crime control field” (Garland, 2001) designed to control the problem populations created by neo-liberal economic policies (Wacquant, 2009a). The paper also suggests that field theory could be usefully deployed in future research to explore how wider global trends or social forces, such as neo-liberalism or bio-power, are refracted through the crime control field in different national jurisdictions. We conclude by showing how this approach provides a bridge between society-wide analysis and micro-sociology by exploring how the operation of new surveillance technologies is mediated by the “habitus” of surveillance agents working in the crime control field and contested by surveillance subjects.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTc2NDUvbWFjLnYzaTIuMjUx